Stabilization of Functional Recombinant Cannabinoid Receptor CB2 in Detergent Micelles and Lipid Bilayers - Vukoti, Krishna; Kimura, Tomohiro; Macke, Laura; Gawrisch, Klaus; Yeliseev, Alexei (PLOS ONE, 2012)
Elucidation of the molecular mechanisms of activation of G protein-coupled receptors (GPCRs) is among the most challenging tasks for modern membrane biology. For studies by high resolution analytical methods, these integral membrane receptors have to be expressed in large quantities, solubilized from cell membranes and purified in detergent micelles, which may result in a severe destabilization and a loss of function. Here, we report insights into differential effects of detergents, lipids and cannabinoid ligands on stability of the recombinant cannabinoid receptor CB2, and provide guidelines for preparation and handling of the fully functional receptor suitable for a wide array of downstream applications. While we previously described the expression in Escherichia coli, purification and liposome-reconstitution of multi-milligram quantities of CB2, here we report an efficient stabilization of the recombinant receptor in micelles - crucial for functional and structural characterization. The effects of detergents, lipids and specific ligands on structural stability of CB2 were assessed by studying activation of G proteins by the purified receptor reconstituted into liposomes. Functional structure of the ligand binding pocket of the receptor was confirmed by binding of 2H-labeled ligand measured by solid-state NMR. We demonstrate that a concerted action of an anionic cholesterol derivative, cholesteryl hemisuccinate (CHS) and high affinity cannabinoid ligands CP-55,940 or SR-144,528 are required for efficient stabilization of the functional fold of CB2 in dodecyl maltoside (DDM)/CHAPS detergent solutions. Similar to CHS, the negatively charged phospholipids with the serine headgroup (PS) exerted significant stabilizing effects in micelles while uncharged phospholipids were not effective. The purified CB2 reconstituted into lipid bilayers retained functionality for up to several weeks enabling high resolution structural studies of this GPCR at physiologically relevant conditions.